On the Relation Between Over-Indebtedness and Well-Being: An Analysis of the Mechanisms Influencing Health, Sleep, Life Satisfaction, and Emotional Well-Being - Ferreira, Mário B.; de Almeida, Filipa; Soro, Jerônimo C.; Herter, Márcia Maurer; Pinto, Diego Costa; Silva, Carla Sofia (Frontiers in Psychology, 2021)
This paper aims to explore the association between over-indebtedness and well-being by examining two of its components — life satisfaction and emotional well-being. Although prior research has associated over-indebtedness with lower life satisfaction, this study contributes to the extant literature by revealing its effects on emotional well-being, a crucial component of subjective well-being that has not, to date, received sufficient attention. The findings suggest that the physical and psychological health of over-indebted (vs. non-over-indebted) consumers are affected in several ways, namely by lower life satisfaction and emotional well-being, poorer (reported) health and sleep quality. Furthermore, over-indebtedness impacts life satisfaction and emotional well-being through different mechanisms. Perceived control fully mediates the relationship between indebtedness status and emotional well-being in addition to reported health. It also partially mediates the relationship between indebtedness status and life satisfaction, and sleep quality. Financial well-being partly mediates the relationship between indebtedness status and life satisfaction. The current study contributes to research focusing on the relationship between debt, well-being, health and sleep quality, and provides relevant theoretical and practical implications.